Implementation Of The Tikrar Method In The Faculty Of Islamic Religion Program To Increase The Competence Of Memory Of The Quran For UMSU Students - Asri Wahyuni (-, 2022)
This research was conducted to find out how the implementation of the Tikrar Method at the Faculty of Islamic Studies Program in Improving the Al-Quran Memorizing Competence of UMSU Students. This research covers planning, implementation and evaluation of the tikrar method. This study used qualitative research methods, and data collection was obtained from the results of observations, interviews and documentation conducted in the field. From the process, it was found that prior to the application of the tikrar method, planning was carried out in advance, namely students had to register to take part in the FAI Qur'an program, students who were required to take part in the program were fourth semester students of the Faculty of Islamic Religion, then socialized the activities and implementation of the program and explained about the method, after that the determination of groups and their mentors is carried out. In its application, the tikrar method is applied by repeating the readings that are the target of memorization at home or on campus, then after memorizing students will deposit it to their respective mentors at each meeting. The evaluation was carried out after the students had successfully completed their memorization, namely juz 30 by depositing all the memorized surahs in juz 30 and the deposit was made in one sitting.